Desain dan Aplikasi Tempat Sampah Puntung Rokok di Pantai Wisata Kondangmerak, Kabupaten Malang: Design and Implementation of Cigarette Butt Trash Bins at Kondangmerak Beach, Malang Regency - Sari, Syarifah Hikmah Julinda; Yona, Defri; Yanuar, Adi Tiya (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The problem of cigarette butts scattered in the Kondangmerak Tourism Beach area, Malang Regency, is a serious concern because of its impact on the environment and coastal ecosystems. Therefore, through community service activities at Kondangmerak Beach, Sumberbening Village, Bantur District, Malang Regency, we will discuss the design and application of special trash bins for cigarette butts as a solution to reduce pollution in the Kondangmerak tourist beach area. The cigarette butt waste disposal bin is made of wood with dimensions of 30 x 50 x 5 cm in the shape of a box and painted yellow. Next, the disposal site is divided into two boxes for disposing of cigarette butts and each box is equipped with a hole the size of the diameter of the cigarette butt for disposal. This design also considers educational aspects through environmental awareness campaigns, to encourage responsible behavior in disposing of cigarette butts in the right place. The application of this trash can involves the active participation of local communities and tourism managers in promoting a clean and healthy environment.